The intermittences of the historical object: criticism of progress and meanings of the revolution in Walter Benjamin - Costa, Gilmário (Sofia, 2022)
This paper aims to investigate the articulation between the critique of progress and the meaning of revolution in the Benjaminian philosophy. They both face the fascist threats of the time and inquiry the motives, means, and possibilities of subverting the Capitalist system. In this way Benjamin do not follow mechanistic Marxist formulations, especially those which were developed during the II International; instead, he relates the meaning of revolution to class struggle. This corresponded to the demand for articulating theory and praxis toward a critique, which was intended as radical, to the bourgeois society. The refusal of the triumphalist image of the progress established the foundation of the concept of revolution and of the critique of the fascism.ResumoEste artigo investiga a articulação entre crítica do progresso e sentidos da revolução na filosofia benjaminiana. É comum a ambos o interesse no questionamento das ameaças fascistas da sua época e o exame dos motivos, meios e possibilidades de subversão do sistema capitalista. Nesse itinerário, Benjamin recusa formulações marxistas mecanicistas, especialmente aquelas desenvolvidas no âmbito da II Internacional, em favor do sentido da revolução relacionado à luta de classes. A isso correspondia a exigência de articulação entre teoria e prática com vistas a uma crítica, que pretendia ser radical, da sociedade burguesa. O questionamento da imagem triunfalista de progresso constituía um fundamento desse conceito de revolução e da crítica ao fascismo.
Keywords: revolution; fascism; history; writing; Walter Benjamin